Stretch-Induced Alkalinization of Feline Papillary Muscle: An Autocrine-Paracrine System - Cingolani, Horacio Eugenio (1998)
Myocardial stretch is a well-known stimulus that leads to hypertrophy. Little is known, however, about the intracellular pathways involved in the transmission of myocardial stretch to the cytoplasm and nucleus. Studies in neonatal cardiomyocytes demonstrated stretch-induced release of angiotensin II (Ang II). Because intracellular alkalinization is a signal to cell growth and Ang II stimulates the Na + /H + exchanger (NHE), we studied the relationship between myocardial stretch and intracellular pH (pH i ). Experiments were performed in cat papillary muscles fixed by the ventricular end to a force transducer. Muscles were paced at 0.2 Hz and superfused with HEPES-buffered solution. pH i was measured by epifluorescence with the acetoxymethyl ester form of the pH-sensitive dye 2′,7′-bis(2-carboxyethyl)-5,6-carboxyfluorescein (BCECF-AM). Each muscle was progressively stretched to reach maximal developed force (L max ) and maintained in a length that was ≈92% L max (L i ). During the “stretch protocol,” muscles were quickly stretched to L max for 10 minutes and then released to L i ; pH i significantly increased during stretch and came back to the previous value when the muscle was released to L i . The increase in pH i was eliminated by (1) specific inhibition of the NHE (EIPA, 5 μmol/L), (2) AT 1 -receptor blockade (losartan, 10 μmol/L), (3) inhibition of protein kinase C (PKC) (chelerythrine, 5 μmol/L), (4) blockade of endothelin (ET) receptors with a nonselective (PD 142,893, 50 nmol/L) or a selective ET A antagonist (BQ-123, 300 nmol/L). The increase in pH i by exogenous Ang II (500 nmol/L) was also reduced by both ET-receptor antagonists. Our results indicate that after myocardial stretch, pH i increases because of stimulation of NHE activity. This involves an autocrine-paracrine mechanism in which protein kinase C, Ang II, and ET play crucial roles.